Insiden Serangan Ulat Grayak Spodoptera frugiperda (Lepidoptera: Noctuidae) pada Tanaman Jagung di Kalimantan Timur - Bayu Widhayasa; Ertha Dwi Prasetyani; Heru Gendroyono (Fapetrik-UMPAR, 2021)
The armyworm Spodoptera frugiperda is a new pest found on maize in Indonesia. Previous research reported that S. frugiperda attacks had occurred in West Sumatra, South Sumatra, Lampung, Banten, West Java, and East Nusa Tenggara. This study aims to determine the presence and determine the attack of S. frugiperda on maize in East Kalimantan. Observations were made from January to December 2020 in the Regencies of Berau, West Kutai, Kutai Kartanegara, North Penajam Paser and Paser. Based on the morphological characteristics, it was confirmed the presence of S. frugiperda larvae with inverted Y-shaped markings on the front of the head, and the presence of black spots forming a square and trapezoidal pattern on the abdomen. Berau Regency experienced the highest S. frugiperda attack in East Kalimantan with an attacking intensity reaching 13.33%. The results of the determination of the attack category showed that 93.31% of S. frugiperda attacks on maize in East Kalimantan were still in the mild category, the rest were in the moderate and severe categories, and there was no dried up incidence.